Magnetic measurement of soft magnetic composites material under 3D SVPWM excitation - Changgeng Zhang; Baolin Jiang; Yongjian Li; Qingxin Yang (AIP Advances, 2018)
The magnetic properties measurement and analysis of soft magnetic material under the rotational space-vector pulse width modulation (SVPWM) excitation are key factors in design and optimization of the adjustable speed motor. In this paper, a three-dimensional (3D) magnetic properties testing system fit for SVPWM excitation is built, which includes symmetrical orthogonal excitation magnetic circuit and cubic field-metric sensor. Base on the testing system, the vector B and H loci of soft magnetic composite (SMC) material under SVPWM excitation are measured and analyzed by proposed 3D SVPWM control method. Alternating and rotating core losses under various complex excitation with different magnitude modulation ratio are calculated and compared.